Design optimization of a 3-stage membrane cascade for oligosaccharides purification using mixed integer non-linear programming - Rizki, Zulhaj; Janssen, Anja E.M.; Hendrix, Eligius M.T.; van der Padt, Albert; Boom, Remko M.; Claassen, G.D.H (Chemical engineering science, 2021)
[Display omitted] •MINLP is used to optimize a 3-stage nanofiltration cascade for FOS purification.•The model selects the optimum membrane, TMP, temperature and area in each stage.•The solutions are used to map the optimum operating conditions in the cascade.•In a 3-stage cascade, the top stage works as the critical separation stage. Inhomogeneous membrane cascade systems have been utilized to purify fructooligosaccharides (FOS). Such a process allows a different setup at every stage of the cascade. Varying the setup at every stage implies an optimization problem related to the selection of the membrane and combinations of operating conditions. This paper solves the optimization problem for an inhomogeneous 3-stage membrane cascade and uses the solution as a design guideline. The optimization problem in the 3-stage membrane cascade design has been formulated as a mixed integer, non-linear programming model and solved using the global optimization solver, BARON. By maximizing the yield repetitively with varying purity requirements, a frontier curve has been constructed. The frontier curve was mapped showing the window of operation. The map guides towards the setup that promotes higher permeation in the feed stage when we switch from high yield to high purity. On the other hand, the setup selection at the bottom stage does not show a clear switch, which indicates that the selection at this stage is less critical.